Current approaches to the management of hepatitis C. Issue 20 (24th October 2013) - Backx, Matthijs; Healy, Brendan
Abstract: Hepatitis C can lead to cirrhosis, decompensated liver disease and hepatocellular carcinoma. The authors discuss today's recommended management and the GP's role in diagnosis, screening and referral.